Effect of larval food amount on in vitro rearing of Indo-Malayan Stingless Bee Queen, Heterotrigona itama (Hymenoptera : Apidae; Meliponini) - Nurul Izdihar Razali,; Shamsul Bahri Abd Razak,; Fatimah Hashim,; Nurul Wahida Othman,; Wahizatul Afzan Azmi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The demand for stingless bee colonies in Malaysia has considerably increased due to the rapid advance of meliponiculture in using the stingless bees as agricultural pollinators, as well as the commercialization of stingless bee products (i.e. honey, bee bread and propolis). Thus, in vitro queen rearing for a large scale and rapid colony multiplication must be developed in order to fulfil the public requirements in a short period. Little is known about the in vitro rearing of native stingless bee queen, Heterotrigona itama. Therefore, in this study, we investigated the amount of larval food required by H. itama queen by comparing three different amounts of larval food, viz., 100 μL, 120 μL and 150 μL. All treatments were controlled under 100% relative humidity for the first 6 days, and 75% relative humidity for the rest of larval development until queen adult emergence, under 30 °C incubator temperature. The results showed that larvae of H. itama treated with the highest amount of larval food (150 μL) led to 78% of the queen’s emergence, whereas larvae treated with 120 μL and 100 μL of larval food resulted in 40% and 0% of queen emergence. The dynamic survival curve showed that most of the larvae died before the pupation phase and reached constant stability afterward. The queen’s body and abdominal length were significantly greater than wild workers. Microscopy analysis showed that in vitro queen had well-developed reproductive system with a huge ovary and spermatheca, whereas wild worker had much smaller ovary without spermatheca. Outcomes from this study could help increase the number of colonies on a large scale, allowing for their use both ecologically and economically, and contribute to conservation efforts in native species of stingless bees.